Using feedforward to improve pre-service teachers’ academic writing and critical thinking skills - Baroudi, Sandra; Aoun, Serena; Hamam, Doaa (Frontiers in Education, 2023)
Literature to date indicates that constructive, timely, and personalized instructor feedback to student work boosts their academic performance. Peer feedback has been investigated extensively for the past three decades and has demonstrated its effectiveness where students were trained to give quality feedback. Little, however, is known about the use of feedforward as a strategy that focuses on future assignments and paves the way to improved performance. This study followed an action research design using a mixed-method approach to examine the impact of feedforward on developing pre-service teachers’ performance on two main skills: critical thinking and academic writing. The teacher researcher followed the same cohort of 14 Emirati pre-service teachers’ over two semesters and used a pre- and post-test to collect quantitative data and a survey to collect qualitative data. Findings in this research study reveal that when using feedforwarding on the same cohort of fourteen pre-service teachers over the period of two academic semesters, their scores on the post-test for the two skills improved. This new strategy promoted their motivation to improve their performance on the next task and enhanced the quality of their work. Findings also highlight potential reasons that inhibited the participants’ ability to create rich assignments that include content-specific vocabulary and to make connections with the course content. This study implies for curriculum designers at the K-12 level to integrate authentic tasks that engage students with real-world problems and train them on inferring information as a scaffold to the development of their critical thinking skills.